303 Adherence to Nil by Mouth Guidelines in A Tertiary Centre. (12th October 2021) - Muscat, E; Fabre, I; Mohiuddin, K
Abstract: Aim: Fasting before general anaesthetic aims to decrease the volume and acidity of stomach contents during surgery, which therefore reduces the risk of aspiration. This is a second cycle closed loop reaudit which had implemented Nil by mouth (NBM) guidelines during the first cycle as an intervention to improve knowledge. Preoperatively, adult patients should remain fasted for a minimum duration as below: Solid food= 6 hours, A cup of milky tea/ fizzy drink= 6 hours, Clear fluids= 2 hours Medications= 30 minutes During the second cycle interventions were included such as: teaching to junior doctors and nurses including specific teaching during induction of new surgical doctors and posters displaying the NBM guidelines were placed in surgical wards. These were carried out despite restrictions during the COVID-19 pandemic. Method: The same questionnaire was redistributed amongst staff members (nurses and HCA) throughout various surgical wards and junior doctors. Results were compared with the initial audit during this second cycle to assess whether any improvements had been made after implementation of interventions. Results: Total number of staff: 56 (63 initial audit) 82% - NBM for 6 hours for meals (37% initial audit), 84% -NBM for 6 hours for drinks with particles (62% initial audit), 91% - 2 hours as the cut off for clear fluids (58% initial audit), 86% - 30 minutes as cut off for medications (55% initial audit). Conclusions: A significant improvement in knowledge and understanding of the NBM guidelines was demonstrated with all members of staff and practice was in accordance with NICE guidelines.